Effects of shot peening pressure on friction and wear of high pressure cold sprayed Ti-6Al-4V coatings under dry and lubrication conditions - Khun, Nay Win (2024)
The effects of shot peening pressure (SPP) (10-60psi) on the wear resistance of high-pressure-cold-sprayed Ti-6Al-4V coatings (HPCSTi64-Coats) were investigated against 100Cr6 steel with or without mineral oil lubricant (MOL), which have not been reported yet. The specific wear rate (SWR) of the HPCSTi64-Coat with the SPP of 60psi was 29% lower than that of the one without shot peening (SP). With the MOL, the SWR of the HPCSTi64-Coat without SP was 40.8% higher than that of the one with 10psi. The SWR of the HPCSTi64-Coat became higher with higher SPP while the SWR of the HPCSTi64-Coat with 60psi was 76.5% higher than that of the one with 10psi. Therefore, the best SPP for the best bearing surface of the HPCSTi64-Coat with the MOL was 10psi. In spite of that, the HPCSTi64-Coats lubricated with the MOL had smaller SWRs for all the SPPs so that the SWRs of the HPCSTi64-Coats with the SPPs of 0 and 60psi were 2.4 and 0.9 times higher, respectively, in the tribo-tests without than with the MOL.